Functional changes in cytotoxic CD8+ T-cell cross-reactivity against the SARS-CoV-2 Omicron variant after mRNA vaccination - Nogimori, Takuto; Suzuki, Koichiro; Masuta, Yuji; Washizaki, Ayaka; Yagoto, Mika; Ikeda, Mami; Katayama, Yuki; Kanda, Hidenori; Takada, Minoru; Minami, Shohei; Kobayashi, Takeshi; Takahama, Shokichi; et al. (Frontiers in Immunology, 2023)
Understanding the T-cell responses involved in inhibiting COVID-19 severity is crucial for developing new therapeutic and vaccine strategies. Here, we characterized SARS-CoV-2 spike-specific CD8+ T cells in vaccinees longitudinally. The BNT162b2 mRNA vaccine can induce spike-specific CD8+ T cells cross-reacting to BA.1, whereas the T-cell receptor (TCR) repertoire usages decreased with time. Furthermore the mRNA vaccine induced spike-specific CD8+ T cells subpopulation expressing Granzyme A (GZMA), Granzyme B (GZMB) and Perforin simultaneously in healthy donors at 4 weeks after the second vaccination. The induced subpopulation was not maintained at 12 weeks after the second vaccination. Incorporating factors that efficiently induce CD8+ T cells with highly cytotoxic activity could improve future vaccine efficacy against such variants.